The tusks of extinction - Nayler, Ray (Tordotcom/Tor Publishing Group, 2024)
"When you bring back a long-extinct species, there's more to success than the DNA. Moscow has resurrected the mammoth. But someone must teach them how to be mammoths, or they are doomed to die out, again. The late Dr. Damira Khismatullina, the world's foremost expert in elephant behavior, is called in to help. While she was murdered a year ago, her digitized consciousness is uploaded into the brain of a mammoth. Can she help the magnificent creatures fend off poachers long enough for their species to take hold? And will she ever discover the real reason they were brought back?" -- Publisher website.